Cross-lagged cross-subject bidirectional predictions among achievements in mathematics, English language and Chinese language of school children - Mok, Magdalena Mo Ching; Zhu, Jinxin; Law, Cecilia Lai Kwan (Educational psychology (Dorchester-on-Thames), 2017)
This study aimed to explore the cross-lagged association of achievements in mathematics and languages. While the effect of language on achievements in mathematics is well-documented, few studies have examined the reciprocal relationships among mathematics, the Chinese language and the English language in the same study. This study conducted a secondary analysis of longitudinal achievement data collected through the Territory-wide System Assessment (TSA) in Hong Kong. The sample comprised 48,547 third-grade, unbalanced bilingual students who were measured three times over six years: in 2007 (in Grade 3), 2010 (Grade 6) and 2013 (Grade 9). Multilevel cross-lagged analysis found prior achievement in a subject was the strongest predictor of achievement in that subject three years later. Furthermore, cross-subject bidirectional prediction was found among achievements in mathematics, Chinese language and English language for students from Grade 3 to Grade 6 and from Grade 6 to Grade 9.